Amputation for chronic pain and/or functional impairment of a limb - Evelyne Linden (Foundation for Rehabilitation Information, 2021)
Objective: To evaluate the impact of a lower limb amputation for chronic pain and/or functional impairment on pain and participation in daily living activities and to assess the use of prostheses. To improve decision-making for this controversial treatment.